Time Dependence of the Effect of Right Ventricular Dysfunction on Clinical Outcomes After Myocardial Infarction: Role of Pulmonary Hypertension. Issue 7 (July 2016) - Shahar, Keren; Darawsha, Wisam; Yalonetsky, Sergey; Lessick, Jonathan; Kapeliovich, Michael; Dragu, Robert; Mutlak, Diab; Reisner, Shimon; Agmon, Yoram; Aronson, Doron
Abstract : Background: The clinical importance of right ventricular (RV) function in acute myocardial infarction is well recognized, but the impact of concomitant pulmonary hypertension (PH) has not been studied. Methods and Results: We studied 1044 patients with acute myocardial infarction. Patients were classified into 4 groups according to the presence or absence of RV dysfunction and PH, defined as pulmonary artery systolic pressure >35 mm Hg: normal right ventricle without PH (n=509), normal right ventricle and PH (n=373), RV dysfunction without PH (n=64), and RV dysfunction and PH (n=98). A landmark analysis of early (admission to 30 days) and late (31 days to 8 years) mortality and readmission for heart failure was performed. In the first 30 days, RV dysfunction without PH was associated with a high mortality risk (adjusted hazard ratio 5.56, 95% CI 2.05–15.09, P <0.0001 compared with normal RV and no PH). In contrast, after 30 days, mortality rates among patients with RV dysfunction were increased only when PH was also present. Compared with patients having neither RV dysfunction nor PH, the adjusted hazard ratio for mortality was 1.44 (95% CI 0.68–3.04, P =0.34) in RV dysfunction without PH and 2.52 (95% CI 1.64–3.87, P <0.0001) in RV dysfunction with PH. PH with or without RV dysfunction was associated with increased risk for heart failure. Conclusion: In the absence of elevated pulmonary pressures, the risk associated with RV dysfunction after acute myocardial infarction is entirely confined to the first 30 days. Beyond 30 days, PH is the stronger risk factor for long‐term mortality and readmission for heart failure.